Design and characterization of sgRNAs aimed at the control of the phytopathogen Pseudocercospora fijiensis that causes Black Sigatoka - Moncayo, Luis; Centanaro, Paulo; Arcos-Jácome, Diego; Castro, Alex; Maldonado, Cristina; Vaca, Diego; González, Gardenia; Lossada, Carla; Perez, Aleivi; González-Paz, Lenin (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Black Sigatoka, caused by the fungus Pseudocercospora fijiensis (Mycosphaerella fijiensis) is an important disease of bananas and plantain. The design of sgRNAs molecules for gene silencing offers the possible control of this phytopathogen. The sgRNAs, are molecules that bind to enzymes to specifically edit genes of interest. The use of these molecules requires the use of bioinformatics tools for their study. Therefore, the objective of this research was to design and characterize sgRNAs to silence the Fus3 virulence gene and CYP51 gene growth in P. fijiensis, through the analysis of structural, thermodynamic and functional characteristics that allow to discriminate the sgRNAs candidates for control of the phytopathogen. Several thermodynamically stable sgRNAs with high specificity for the target genes were achieved, as well as with sequences easily recognizable by the SpCas9 nuclease, and with sizes that allow efficient diffusion in eukaryotic cytoplasms. The results suggest that all the designed and characterized sgRNAs can promote the correct silencing of the genes selected for the control of P. fijiensis. Additionally, the most optimal designs were identified, based on the characteristics considered in this study. These results, although they require additional studies to improve the technology, are promising as they show the possibility of using non-toxic and highly specific molecular tools in plant biotechnology for genetic improvement, directed mutagenesis, plant sanitation and control of phytopathogens.